Qualitative Study on Data Integration Challenges for Implementing CRM in Health Promotion at Indonesian Primary Health Care - Wijaya, Avid; Zein, Eiska Rohmania; Caesar Putra, Muhammad Dudayev; Rusdi, Achmad Jaelani; Sangkot, Hartaty Sarma (Informatika, Universitas Jenderal Soedirman, 2025)
Primary health care (PHC) is increasingly required to implement targeted, adaptive, and evidence-based health promotion in line with the growth of digital health technologies. Nevertheless, the utilization of routine medical record data as a foundation for Customer Relationship Management (CRM) to support health promotion in PHC remains limited. Key constraints include fragmented information systems, high data processing burdens, and restricted analytic capacity. This study aimed to explore existing practices, barriers, and system development needs related to medical record based CRM to strengthen data-driven health promotion, with particular attention to data integration. A qualitative exploratory study was conducted in 2025 at PHC Wagir, Malang District, Indonesia. Data were obtained through semi-structured in-depth interviews with two key informants: a health promotion officer and a medical record and health information (RMIK) officer. Thematic analysis focused on five domains: current systems, use of data in PHC programs, challenges in data provision and utilization, information system requirements, and expectations for system development. The findings indicate that health promotion data are dispersed across multiple non-integrated applications, leading to double data entry, spreadsheet-based reprocessing, limited filtering, and minimal trend analysis or target segmentation. System instability and limited human resources further constrain analytic use. Informants emphasized the need for an integrated “single window” system featuring automated summaries, flexible filtering, disease trend visualization, multiuser access, and cross program integration. This study advances informatics in public health by proposing a socio technical framework for data-driven CRM implementation in resource limited primary care settings.